Evaluation of a miniaturised single-stage thermal modulator for comprehensive two-dimensional gas chromatography of petroleum contaminated soils - Jacobs, MR; Edwards, M; Gorecki, T; Nesterenko, PN; Shellie, RA (Journal of Chromatography A, 2016)
A novel miniaturised single-stage resistively heated thermal modulator wasinvestigated as an alternative to cryogenic modulation for use in comprehensive two dimensionalgas chromatography (GC GC). The single-stage thermal modulator describedherein yielded average retention time relative standard deviations (RSD) of ≤ 0.2 % RSD(first-dimension) and ≤ 3.4 % RSD (second-dimension). The average peak widths generatedby the modulator were 72 3 ms, and the peak area precision was better than 5.3 % RSD fora range of polar and non-polar test analytes. GC GC analysis can be performed using thismodulator without the requirement for cryogenic cooling or additional pressure controlmodules for flow modulation. The modulator and associated electronics are compact andamenable towards field analysis. The modulator was used for qualitative and quantitativecharacterisation of petroleum-contaminated soils derived from a sub-Antarctic researchstation at Macquarie Island. The limit of detection compared to standard 1D GC analysis wasimproved from 64 to 11 mg kg-1. An automated method of analysing and categorising samplesusing principal component analysis is presented.